Análise da distribuição de recursos minerais metálicos no cinturão Dom Feliciano, através de dados geológicos, aerogeofísicos e de sensoriamento remoto - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The Dom Feliciano Belt is composed of the Santa Catarina and Sul-Rio-Grandense shields, which are geographically discontinuous, due to the covers of the Paraná Basin. The terrenes that make up them, contain significant mineral occurrences, such as Au, Sn, W metal mineralizations and base metal sulfides (Cu, Pb, Zn) that occur associated or not, with precious metals (Au, Ag). It is notorious that these metal mineralizations have strong structural control, where they usually occur, associated with fault zones. The objectives of this study are the identification of structural features that may be associated with the distribution of metallic mineral resources in the terrains that make up the shields. To achieve these purposes, the methodology adopted consisted of a bibliographic survey about the mineral occurrences, deposits and mines that exist in the areas; analysis, interpretation and extraction of linear features through Sentinel-2 images and aerogeophysical data of gamma-spectrometry and magnetometry. All these elements were integrated into a Geographic Information System (GIS), allowing an integrated data analysis. The lineaments defined through the aerogeophysical data were overlapped, resulting in the generation of shield lineament maps, where it was possible to recognize the structural trends of each geotectonic domain, referred in already consolidated bibliographies. In both shields, it was observed that the metallic resources tend to concentrate in certain terrains, coinciding with those with higher lineament densities. Some areas were pointed for more detailed studies, such as the application of terrestrial geophysics, in function of are located near areas containing deposits and mines, and present similar patterns to these.
Keywords: Exploração mineral; Mineralizações metálicas; Lineamentos; Mineral exploration; Metal mineralizations; Lineaments; CNPQ::CIENCIAS EXATAS E DA TERRA